Adsorption of Mg (II) Ion Using Chlorophilized Chitin Adsorbent - Darjito Darjito; Rachmat Triandi; Diah Mardiana; M. Fathoni (Natural B, Journal of Health and Environmental Sciences, 2013)
A study concerning the adsorption of Mg (II) ions using phosporilation chitin adsorbent. The process is a surface modification of adsorbent chitin by enriching the phosphate group that acts as a hard base so it would be more suitable binding Mg (II) ions, which acts as a hard acid. This research aims to study the effect of contact time and concentration variations of Mg (II) ions on the adsorption process using phosporilation chitin adsorbent. Variables to be examined in this study in order are contact times (40, 60, 80, 100, and 120 minutes) and the concentration of Mg (II) ions variation are (10, 25, 50, 75, 100, 125, 150, 175, and 200 ppm). The results for the characterization of phosporilation chitin adsorbent can be detect from the IR absorption band at wavenumber 1099.35 cm-1 are suspected of phosphate ions and IR absorption band at wave number 1272.93 cm-1 and 1201.57 cm-1 are estimated as phosphate covalent. The contacts times significantly affect the adsorption Mg (II) ions by the phosporilation chitin adsorbent, then the optimum of contact time is 120 minutes. Adsorption capacity of phosporilation chitin adsorbent for the Mg(II) ions is 499 mg/g.